Opsoclonus-Myoclonus Syndrome in Children and Adolescents: A Therapeutic Challenge - Marina Auconi (MDPI AG, 2021)
Opsoclonus-myoclonus syndrome (OMS) is a neurological non-fatal disease that usually responds to immunotherapies. However, the real challenge is to counteract the high frequency of relapses and long-term developmental sequelae. Since the OMS is extremely rare, a common consensus regarding therapeutic guidelines is still lacking. The goals of this study were to test whether ACTH was superior to other immunotherapies and to investigate whether an early treatment could improve the outcome. Sixteen children affected by OMS were retrospectively reviewed. Eight children had a neuroblastic tumor. The other eight patients were affected by non-paraneoplastic OMS. Overall, the most commonly used treatment was corticotherapy (n = 11). However, ACTH (n = 10), rituximab (n = 7), immunoglobulins (n = 4), cyclophosphamide (n = 3), and mycophenolate (n = 2) were also administered. ACTH was associated with a high percentage of patients who healed (80%) and, as a first-line therapy, was associated with a lower incidence of relapses. An early treatment was associated with a favorable long-term outcome. Long-term sequelae occurred in 42% of patients who were treated early and in all of those who were treated late. It is advisable for the affected children to be identified at an early time, as they may benefit from an early treatment. ACTH represents an effective treatment with a high probability of recovery and low rate of relapses.